Comparing Fear of COVID-19 and Preventive COVID-19 Infection Behaviors Between Iranian and Taiwanese Older People: Early Reaction May Be a Key - Pakpour, Amir H.; Liu, Chieh-hsiu; Hou, Wen-Li; Chen, Yu-Pin; Li, Yueh-Ping; Kuo, Yi-Jie; Lin, Chung-Ying; Scarf, Damian (Frontiers in Public Health, 2021)
This study assessed fear of the novel coronavirus-2019 (COVID-19), preventive COVID-19 infection behaviors, and the association between fear of COVID-19 and preventive COVID-19 infection behaviors among older people in Iran and Taiwan. Older people aged over 60 years (n = 144 for Iranians and 139 for Taiwanese) completed the Fear of COVID-19 Scale (FCV-19S) and two items on preventive COVID-19 infection behaviors (i.e., hand washing and mouth covering when sneezing). Iranian older people had a significantly higher level of fear of COVID-19 than did Taiwanese older people. Moreover, Iranian older people had significantly lower frequencies of preventive COVID-19 infection behaviors than did Taiwanese older people. Different timings in implementing COVID-19 infection control policies in Iran and Taiwan may explain why Iranian older people had greater fear of COVID-19 and lower preventive COVID-19 infection behaviors than did Taiwanese older people.